Reassessment of the NH4NO3 thermal decomposition technique for calibration of the N2O isotopic composition. (20th October 2016) - Mohn, Joachim; Gutjahr, Wilhelm; Toyoda, Sakae; Harris, Eliza; Ibraim, Erkan; Geilmann, Heike; Schleppi, Patrick; Kuhn, Thomas; Lehmann, Moritz F.; Decock, Charlotte; Werner, Roland A.; Yoshida, Naohiro; et al.
Abstract : Rationale: In the last few years, the study of N2 O site‐specific nitrogen isotope composition has been established as a powerful technique to disentangle N2 O emission pathways. This trend has been accelerated by significant analytical progress in the field of isotope ratio mass spectrometry (IRMS) and more recently quantum cascade laser absorption spectroscopy (QCLAS). Methods: The ammonium nitrate (NH4 NO3 ) decomposition technique provides a strategy to scale the 15 N site‐specific (SP ≡ δ 15 N α – δ 15 N β ) and bulk (δ 15 N bulk = (δ 15 N α + δ 15 N β )/2) isotopic composition of N2 O against the international standard for the 15 N/ 14 N isotope ratio (AIR‐N2 ). Within the current project 15 N fractionation effects during thermal decomposition of NH4 NO3 on the N2 O site preference were studied using static and dynamic decomposition techniques. Results: The validity of the NH4 NO3 decomposition technique to link NH4 + and NO3 − moiety‐specific δ 15 N analysis by IRMS to the site‐specific nitrogen isotopic composition of N2 O was confirmed. However, the accuracy of this approach for the calibration of δ 15 N α and δ 15 N β values was found to be limited by non‐quantitative NH4 NO3 decomposition in combination with substantially different isotope enrichment factors for the conversion of the NO3 − or NH4 + nitrogen atom into the α or β position of the N2 O molecule. Conclusions: The study reveals that the completeness and reproducibility of the NH4 NO3 decomposition reaction currently confine the anchoring of N2 O site‐specific isotopic composition to the international isotope ratio scale AIR‐N2 . The authors suggest establishing a set of N2 O isotope reference materials with appropriate site‐specific isotopic composition, as community standards, to improve inter‐laboratory compatibility. Copyright © 2016 John Wiley & Sons, Ltd.